Validation of a New Saliva Test for Helicobacter pylori Infection - OF Bathe; AJ Rae; P Zetler; IGM Cleator (Canadian Journal of Gastroenterology)
The purpose of this study was to evaluate a recently introduced saliva test measuring immunoglobulin (Ig) G antibodies to Helicobacter pylori by enzyme-linked immunosorbent assay (ELISA). ELISA has previously been validated against IgG serological tests; however, it is not considered the definitive test for H pylori infection. Using endoscopic antral biopsies as the ’gold standard’ for comparison, the saliva test was validated on 70 patients with upper gastrointestinal symptoms admitted to St Paul’s Hospital Gastroenterology Clinic for gastroduodenoscopy. Thirty-five patients (50%) had histological evidence of gastritis and, by using acridine orange stain, the bacterium was visualized in 25 patients (71%). A biopsy was considered positive when the bacterium was visualized. The saliva test was determined to be 80% sensitive and 80% specific for H pylori infection when the cut-off for a positive test was 0.3 ELISA U/mL. Positive and negative predictive values were 69% and 88%, respectively. More study is required to assess the clinical utility of the test.